Dampak Pola Asuh Fatherless dalam Al-Qur'an: Study Kritis Parenting dalam Kisah Nabi Ya'kub - Nur Hamimah; Wiwin Ainis Rohtih; Amir Mahmud (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to investigate the impact of fatherless parenting as depicted in the Qur'an, especially through the story of the Prophet Ya'qub. The research method used is a critical analysis of parenting practices seen in the narrative of the Koran, with a focus on the role and influence of fathers in shaping the character of their children. This research describes fatherless parenting in the context of the life of the Prophet Ya'qub, who is the central figure in a complex and intriguing family story in the Qur'an. The results of the analysis highlight the various impacts that arise due to the absence of a father figure in the process of forming children's character. One of the main findings is the importance of the father's role as a family leader who provides moral direction and emotional support to children. Father absence can cause emotional instability and internal conflict in children and increase the risk of them falling into negative behavior. Apart from that, this research also explores the Prophet Ya'qub's efforts to overcome the challenges he faced as a single father. An in-depth analysis of the strategies used by the Prophet Ya'qub in raising his children provides valuable insight into the importance of a father's presence and influence in the family. The findings of this research provide an important contribution to our understanding of the importance of fathers' roles in the process of children's character formation, as well as their implications for contemporary parenting practices. The practical implications of this research include a better understanding of fatherless parenting and efforts that can be made to overcome its negative impacts in modern society.